Structural performance evaluation of horizontally light reinforced dapped for vertical wall-to-wall connection of precast wall panel - Amril Hadri Jamaludin,; Noorsuhada Md Nor,; Amir Khomeiny Ruslan, (Fakulti Kejuruteraan ,UKM,Bangi., 2023)
Precast concrete buildings in Industrialised Building Systems (IBS) are constructed of multiple pieces of structural members joined together using a variety of methods. The use of precast concrete wall panels has become increasingly popular in modern construction practices. One critical aspect of precast concrete wall panels is their connection to the adjacent walls. Various of wall-to-wall connections have been used in the IBS based construction. However, for non-load bearing application, the use of dapped connections for precast wall made with recycled concrete aggregate (RCA) is still limited and unexplored. This study aims to evaluate the structural performance of horizontally light reinforced dapped (HLRD) connections for precast wall panels made with RCA. The investigation includes experimental testing that includes three pair of specimens subjected to uniformly distributed monotonic loading to evaluate their strength capacity, strain, and deflection behaviour as well as the resulting crack propagation throughout the test. The connection displays brittle behaviour by developing a few line cracks and having a significant deflection before failure. The findings of this study will contribute to a better understanding of the behavior of HLRD connections and provide preliminary guidance for their design in precast concrete wall panels.